Cross-Compatibility Between Some Cultivated Cowpea Varieties and a Wild Relative (Subsp. Dekindtiana Var Pubescens) - Nwosu, D. J.; Awa, E. N. (Journal of Scientific Research, 2012)
Four cultivated cowpea (Achi shuru, Ife Brown, Kanannado and Zebra bean) were crossed to their wild relative subsp. dekindtiana var. pubescens to ascertain their cross compatibility, reproductive potential and possible heterosis in the F1 generations. Results show that the cultivated varieties hybridized relatively well with their wild relative with pod set of 40.8% to 46.7%. F1 hybrid plants also showed high heterosis in plant height and number of leaves and produced viable seeds. These results are indications of a good reproductive potential of the hybrids thus making the wild, good candidate for transfer of important gene pool into the cultivated populations. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.10761 J. Sci. Res. 5 (1), 195-200 (2013)